KONVERGENSI MEDIA DIGITAL: TINJAUAN KRITIS DAN IMPLEMENTASINYA DALAM KOMUNIKASI MASSA KONTEMPORER - Tenku, Hefri Yodiansyah; Artuti Erda De, Susi; Kurniadi, Debby (Telkom University, 2025)
This study aims to critically examine the implications of media convergence in contemporary mass communication practices. Media convergence, as the integration process between conventional and digital media, has fundamentally transformed how information is produced, distributed, and consumed by the public. Using a qualitative descriptive approach through library research, this study analyzes the impact of convergence on media structures, audience roles, and the professionalism of journalism in the digital era. The findings indicate that convergence fosters the creation of a cross-platform, real-time, and participatory communication ecosystem. Audiences now act as prosumers (producer-consumers) who actively engage in disseminating and generating content. Meanwhile, journalists are required to master multiplatform skills but face challenges related to production speed, information accuracy, and ethical dilemmas within a highly competitive digital environment. Furthermore, social media algorithms shape information consumption patterns that are vulnerable to disinformation and the polarization of public opinion. Therefore, media convergence should not be viewed merely as a technological phenomenon, but as a complex socio-cultural process. This transformation demands strategic responses from various stakeholders, including enhanced digital literacy, adaptive media policies, and strengthened journalistic standards to ensure that convergence truly supports information democratization and the quality of public communication. Keywords: digital journalism, media literacy, mass communication, media convergence,prosumer